Amelioratory Effect of Vitamin D3 on some Liver Function and Histological Alterations in Experimentally Obese Albino Rats - Mohamed, Osman E.; Nabil, Zohour I.; Mahmoud, Manal M.A.; Gad El-Hak, Heba N.; Abdelrazek, Heba M.A. (Journal of Advanced Veterinary Research, 2024)
Obesity is a global public health issue. It is associated with a spectrum of liver abnormalities, like nonalcoholic fatty liver disease (NAFLD). The purpose of this study was to investigate the effect of Vitamin D3 on light microscopic changes in the liver, as well as hematology and some liver enzymes in experimentally overweight albino rats. Five groups of thirty-five male albino rats were formed. For three months, Control (C) group received a standard laboratory diet. Corn oil (CO) group received normal balanced diet and given orally 20 mg/kg corn oil daily. Vitamin D (D) group received normal balanced diet and orally treated daily with 5000 IU/kg of vitamin D3. Overweight (OW) group rats received high caloric diet. Overweight/ vitamin D (OWD) group received high caloric diet and treated with oral vitamin D3 5000 IU/kg daily. Liver weights of animals were recorded, blood samples for hematology, some liver functions, catalase (CAT) and total antioxidant capacity (TAC) were collected. Liver samples were fixed in 10% formal saline then stained by H&E for histological examination. OW group had significantly higher liver weights, and liver function than CO group. Histologically, there was an increase of fatty degeneration in the OW group. However, OWD group was lower in all the measured and examined liver parameters than that of CO group in this study vitamin D3 supplement could ameliorate the abnormal changes in the hepatocytes induced by obesity.